Formulation of the optimization problem for engine mount design – tractor propeller case. Issue 3 (29th April 2014) - Goetzendorf-Grabowski, Tomasz
Abstract : Purpose: – The aim of this work was to focus on the creation of a mathematical model for the optimization problem and the methodology for selection of the most important parameters. The engine mount design optimization problem requires a selection of the most important parameters, which influence the final solution. Design/methodology/approach: – A two-tier optimization algorithm was considered. The geometry of the engine mount is optimized by first taking into account the sum of loads, and the weight is minimized next. Findings: – Several parameters were selected as the essential set of factors for the engine mount design and for optimization to get the minimal weight for the system of the engine and engine mount. Research limitations/implications: – As a case study, the single turboprop engine attached to the front part of fuselage – the so-called tractor propeller configuration – was considered. Practical implications: – This paper contains the proposed methodology, which is going to be used in the efficient systems and propulsion for small aircraft (ESPOSA) project to optimize the newly designed engine mount. Originality/value: – This paper presents a new developed methodology that could be useful for engine mount design.